2015
DOI: 10.1007/s11249-015-0582-6
|View full text |Cite
|
Sign up to set email alerts
|

FZG Gear Efficiency and Pin-on-Disc Frictional Study of Sintered and Wrought Steel Gear Materials

Abstract: Load-dependent power loss is a major contributor to power loss in gear transmission systems. In this study, pin-on-disc frictional and FZG efficiency experiments were conducted with powder metallurgy (Distaloy AQ ? 0.2 %C) and wrought material (16MnCr5) combinations. The gear mesh torque loss from gear efficiency tests and the friction coefficient from the pin-on-disc tests were then compared. The trend for both test series was the same. The combination of 16MnCr5 in contact with Distaloy AQ ? 0.2 %C shows the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…This is mainly because fewer surface peaks are in contact for the superfinished gears. Note that the mechanism of the difference in efficiency between RS-RS and AQ-AQ ground gear combinations was studied in detail in [14], and will not be discussed here.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is mainly because fewer surface peaks are in contact for the superfinished gears. Note that the mechanism of the difference in efficiency between RS-RS and AQ-AQ ground gear combinations was studied in detail in [14], and will not be discussed here.…”
Section: Discussionmentioning
confidence: 99%
“…8 shows an optical micrograph of a cut section of the AQ material gear tooth showing porosities on or near the surface. Li et al [14] showed that the porosities of AQ can lower the friction coefficient of pin-on-disc experiment and gear mesh torque loss of FZG gear efficiency experiment. Fig.…”
Section: Surface Analysismentioning
confidence: 99%
See 3 more Smart Citations